Difficulties of Students' in Studying Arabic at Baitul Mustaqim Islamic Boarding School Central Lampung |Kesulitan Santri dalam Maharah Kitabah Bahasa Arab di Pondok Pesantren Baitul Mustaqim Lampung Tengah - Apriliana, Vina; Amalia, Dian Risky; Hasanah, Luluk Muhidatul (NAJAH BESTARI, 2024)
Language is a tool used to communicate between humans both verbally and in writing. In class learning, there are also students who have difficulty writing Arabic. There are many difficulties or problems with the Maharah of the Book in learning Arabic experienced by students or santri. Therefore, the researcher discusses the difficulties of maharah kitabah in learning Arabic at the Baitul Mustaqim Islamic boarding school. This research uses a qualitative approach with library study techniques and data collection using observation. The results of the research show that some of the students at the Baitul Mustaqim Islamic boarding school still experience difficulties in understanding the Kitabah. Therefore, the solution to overcome students' difficulties in writing Arabic is to increase students' motivation regarding the importance of writing Arabic, try to use suitable methods, strategies and media, always provide Arabic writing practice every class hour, and always provide language writing assignments. Arabic so that students learn to write not only in class.